A waste-based circular economy approach for phycoremediation of X-ray developer solution. (1st January 2023) - Sharma, Swati; Kant, Anil; Sevda, Surajbhan; Aminabhavi, Tejraj M.; Garlapati, Vijay Kumar
Abstract: A waste-based circular economy approach is proposed for the phycoremediation of an X-ray developer (XD) solution. The present study emphasizes the utilization of food waste (FW) and agri-compost media (ACM) as growth media for D. armatus for the subsequent bioremediation potential of XD solution-coupled lipid production. A 3:1 dilution (FW/ACM: XD.) was found to be suitable for the phycoremediation study of XD solution towards the % removal of biological oxygen demand (BOD), chemical oxygen demand (COD) and silver. The phycoremediation studies of diluted XD solution in FW demonstrated a 74.50% BOD removal, 81.69% COD removal, and 54.70% removal of silver. The growth of D. armatus in diluted XD solution in food waste was 1.37% lipid content. The phycoremediation of diluted XD solution with ACM resulted in 83.05% BOD removal, 88.88% COD removal and 56.30% silver removal with the concomitant lipid production of 1.42%. The optimal bioremediation coupled lipid production of D. armatus was observed on the 19th day of D. armatus cultivation in the developer effluent, along with food waste and agri-compost media, for 31 days. The study suggests a sustainable utilization of waste (FW and ACM) as a nutritive medium to scrutinize the phycoremediation of XD solution with a concomitant lipid production that can open up new avenues in phycoremediation coupled energy commodities production. Graphical abstract: Image 1 Highlights: Proposed waste-based circular economy for phycoremediation. Silver removal (43.69%) possible with D. armatus grown in agri-compost medium. Lipid found with D. armatus grown in agri-compost and food waste media. BOD (83.05%) and COD (88.88%) removal was possible with agro-compost media.